(untitled) (Revista de Crítica Literaria Latinoamericana, 2013)
In the shift from "magical realism" to the "visceral or dirty realism," urban violence has become the main narrative —almost par excellence—of "Latin-American" literature of the 21st century. Nevertheless, there are writers who have dared to defy this trend, turning instead to rewriting an almost forbidden scene. Among them is Juan Gabriel Vásquez, whose novel Secret History of Costaguana, represents an inversion of the magical-realism paradigm, since here the foundation of cities and technological advances (the train, the interoceanic canal, etc.) built in the jungle confirm the Benjaminian judgment: "There has never been a document of culture, which is not simultaneously one of barbarism." In Vasquez ’s work, Nature acquires power as destroyer, which, unlike in the magical narrative, allows for the discovery of a foundational violence that has been covered over. In this novel, magic is replaced by revenge.